CircHMGCS1 is upregulated in colorectal cancer and promotes proliferation of colorectal cancer cells by targeting microRNA-503-5p. (August 2019) - Dong, Jingqing; Li, Jun; Luo, Jihui; Wu, Weiqiang
This study aims to explore the regulatory mechanism of circHMGCS1/microRNA-503-5p (miR-503-5p) axis during colorectal cancer (CRC) development and progression. Real-time quantitative polymerase chain reaction (RT-qPCR) was applied to evaluate the expression of circHMGCS1 and miR-503-5p in CRC samples and their adjacent non-tumor specimen. Then, cell proliferation and cell apoptosis and migration and invasion of circHMGCS1-knocked down cells were further detected, using cell counting kit-8 (CCK-8), flow cytometry, Transwell assay, and western blotting assays. CircHMGCS1 was found to be significantly upregulated in CRC, and its high expression was closely correlated with the poor clinical parameter. In addition, the knockdown of circHMGCS1 could significantly inhibit CRC cells' growth promoting apoptosis, as suggested by the expression of apoptosis pathway-related proteins, which changed consistently. Furthermore, miR-503-5p inhibitors were able to reverse the suppression of cell proliferation induced by silencing circHMGCS1. Therefore, circHMGCS1 might serve as a promising bio-marker and treatment target for CRC.